Evaluation and comparison of late reverberation power spectral density estimators - Braun, Sebastian; Kuklasinski, Adam; Schwartz, Ofer; Thiergart, Oliver; Habets, Emanuel; Gannot, Sharon; Doclo, Simon; Jensen, Jesper (IEEE/ACM Transactions on Audio, Speech, and Language Processing, 2018)
Reduction of late reverberation can be achieved using spatio-spectral filters, such as the multichannel Wiener filter. To compute this filter, an estimate of the late reverberation power spectral density (PSD) is required. In recent years, a multitude of late reverberation PSD estimators have been proposed. In this paper, these estimators are categorized into several classes, their relations and differences are discussed, and a comprehensive experimental comparison is provided. To compare their performance, simulations in controlled as well as practical scenarios are conducted. It is shown that a common weakness of spatial coherence-based estimators is their performance in high direct-to-diffuse ratio conditions. To mitigate this problem, a correction method is proposed and evaluated. It is shown that the proposed correction method can decrease the speech distortion without significantly affecting the reverberation reduction.